The Development of Scaffolding in Inquiry-Based Learning to Improve Students' Science Process Skills in The Concept of Acid and Base Solution - Syafira Tiaradipa; Intan Lestari; M. Haris Effendi; M. Rusdi (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
The technique of providing learning support in a structured manner to encourage students to learn independently is called scaffolding. This consists of four types questioning, prompting, cueing, and explaining. This study aims to describe the procedure for developing scaffolding in inquiry-based learning that is beneficial to improve students' science process skills in the concept of acid and base solution. The heuristic method in the type of F2-O3-S1+S5+S6-A3 was used in this study to develop the design of the scaffolding. The data were collected using an interview and analyzed using a Delphi technique. Based on the expert validation, it was seen that the scaffolding technique designed was suitable for use. The results of the student trial also showed that the scaffolding technique was effective to be used to improve students' science process skills. It can be concluded that the scaffolding technique on inquiry-based learning was able to improve students' science process skills in the concept of acid and base solution.